Reprogrammer la smart city : le quotidien des habitants de Songdo en Corée du Sud - Suzanne Peyrard (Netcom)
In the late 2000s, the smart city model became central for urban planners, particularly in East Asia, where large-scale projects like Songdo in South Korea were being developed. This article, based on ethnographic research conducted between 2018 and 2024, explores the reasons why residents chose to move in this new city of Songdo. Far from being drawn by its smart city status, their choice appears to be rooted in classic factors of residential mobility, such as professional or educational opportunities. Observations and interviews further reveal that functioning smart technologies, such as waste sorting containers or home automation systems, often remain invisible or unused in inhabitants’ daily life. However, these technologies are sometimes repurposed or even reprogrammed by "expert" residents, highlighting a form of appropriation that diverges from the designers’ original intentions.